Determinants Influence The Adoption of M-Commerce in Indonesia : An Empirical Study - Nur Budi Nugraha (Journal of Telematics and Informatics, 2018)
The use of the internet for shopping has been developing increasingly rapid. In 2014 the number of internet users shows numbers 88.1 millions of users. Along with the presence of mobile devices that provide convenience for consumers to access the online sales sites, users who access either using cellular phones to dominate with a percentage of the amount of 85%. M-Commerce provides products and services through mobile devices in the enterprise and improvement of influencing signifkan more specific help companies and also customers, in terms of buying and selling activity. The rate of adoption of M-Commerce has been in developing countries are already good enough. This study focuses on the theoretical grounding against the factors that influence the adoption of M-Commerce. The study used a literature review for identify the various factors that affect the utilization of M-Commerce by consumers. This research takes the case studies in Indonesia as one of the developing countries. The results of this research will provide feedback to companies that adopt M-Commerce to formulate a marketing strategy and developing the appropriate application